Therapeutic conserved elements (CE) DNA vaccine induces strong T-cell responses against highly conserved viral sequences during simian-human immunodeficiency virus infection - Paul Munson; Yi Liu; Debra Bratt; James T. Fuller; Xintao Hu; George N. Pavlakis; Barbara K. Felber; James I. Mullins; Deborah Heydenburg Fuller (Taylor & Francis Group, 2018)
HIV-specific T-cell responses play a key role in controlling HIV infection, and therapeutic vaccines for HIV that aim to improve viral control will likely need to improve on the T-cell responses induced by infection. However, in the setting of chronic infection, an effective therapeutic vaccine must overcome the enormous viral genetic diversity and the presence of pre-existing T-cell responses that are biased toward immunodominant T-cell epitopes that can readily mutate to evade host immunity and thus potentially provide inferior protection. To address these issues, we investigated a novel, epidermally administered DNA vaccine expressing SIV capsid (p27Gag) homologues of highly conserved elements (CE) of the HIV proteome in macaques experiencing chronic but controlled SHIV infection. We assessed the ability to boost or induce de novo T-cell responses against the conserved but immunologically subdominant CE epitopes. Two groups of animals were immunized with either the CE DNA vaccine or a full-length SIV p57gag DNA vaccine. Prior to vaccination, CE responses were similar in both groups. The full-length p57gag DNA vaccine, which contains the CE, increased overall Gag-specific responses but did not increase CE responses in any animals (0/4). In contrast, the CE DNA vaccine increased CE responses in all (4/4) vaccinated macaques. In SIV infected but unvaccinated macaques, those that developed stronger CE-specific responses during acute infection exhibited lower viral loads. We conclude that CE DNA vaccination can re-direct the immunodominance hierarchy towards CE in the setting of attenuated chronic infection and that induction of these responses by therapeutic vaccination may improve immune control of HIV.